(untitled) (Annals of the University of Bucharest. Philosophy Series, 2025)
This paper presents transhumanism as a post-biological philosophy that can provide a theoretical framework for scientific programmes oriented towards the search for intelligent life in the universe. The long-term thinking inherent in transhumanism synchronizes evolution and technology, heralding the genesis of post-biological entities. The first part of the paper assesses the applicability of this scheme to possible alien civilizations older than our own. The second part considers the most intriguing fictional explorations of mind uploading as a possible resolution of the Fermi’s Paradox.